Synthesis of a Fluorine‐Containing Cis‐Cisoidal One‐Handed Helical Polyphenylacetylene and Application of Highly Selective Photocyclic Aromatization Product on Oxygen Permselective Membrane. Issue 8 (28th March 2015) - Zang, Yu; Yin, Guanwu; Aoki, Toshiki; Teraguchi, Masahiro; Kaneko, Takashi; Ma, Liqun; Jia, Hongge
Abstract A novel phenylacetylene monomer having a perfluorinated alkyl group (M-F) was synthesized and polymerized in a chiral catalytic system to yield a one‐handed helical polymer. The ability and efficiency of the chiral induction of the fluorine‐containing monomer in the helix‐sense‐selective polymerization (HSSP) was much higher than those of a monomer having the corresponding alkyl group (M-H) we reported before. The resulting polymer P-F showed cis‐cisoidal one‐handed helical conformation, and was suitable for highly selective photocyclic aromatization (SCAT) to give a 2D surface modifier (T-F). Oxygen permselectivity through a base polymer membrane was highly enhanced from 1.83 to 2.36 by adding a small amount (1–5 wt%) of the 2D surface modifier T-F. The improvement was thought to be caused by improvement of solution selectivity on the membrane surface which the 2D surface modifier effectively covered. Chirality 27:459–463, 2015. © 2015 Wiley Periodicals, Inc.